Neuronal vacuolation and spinocerebellar degeneration associated with altered neurotransmission - Giannakopoulou, Aggeliki (Folia Neuropathologica, 2017)
Inherited neurodegenerative disorders are debilitating diseases that occur across different species, such as the domestic dog (Canis lupus familiaris), and many are caused by mutations in the same genes as corresponding human conditions. In the present study, we report an inherited neurodegenerative condition, termed ‘neuronal vacuolation and spinocerebellar degeneration’ (NVSD) which affects neonatal or young dogs, mainly Rottweilers, which recently has been linked with the homozygosity for the RAB3GAP1:c.743delC allele. Mutations in human RAB3GAP1 cause Warburg micro syndrome (WARBM), a severe developmental disorder characterized predominantly by abnormalities of the nervous system including axonal peripheral neuropathy. RAB3GAP1 encodes the catalytic subunit of a GTPase activator protein and guanine exchange factor for Rab3 and Rab18 proteins, respectively. Rab proteins are involved in membrane trafficking in the endoplasmic reticulum, autophagy, axonal transport and synaptic transmission. The present study attempts to carry out a detailed histopathological examination of NVSD disease, extending from peripheral nerves to lower brain structures focusing on the neurotransmitter alterations noted in the cerebellum, the major structure affected. NVSD dogs presented with progressive cerebellar ataxia and some clinical manifestations that recapitulate the WARBM phenotype. Neuropathological examination revealed dystrophic axons, neurodegeneration and intracellular vacuolization in specific nuclei. In the cerebellum, severe vacuolation of cerebellar nuclei neurons, atrophy of Purkinje cells, and diminishing of GABAergic and glutamatergic fibres constitute the most striking lesions. The balance of evidence suggests that the neuropathological lesions are a reaction to the altered neurotransmission. The canine phenotype could serve as a model to delineate the disease-causing pathological mechanisms in RAB3GAP1 mutation.